Learning curve of endoscopic pituitary surgery: Experience of a neurosurgery/ENT collaboration. (January 2018) - Lofrese, Giorgio; Vigo, Vera; Rigante, Mario; Grieco, Domenico Luca; Maresca, Maddalena; Anile, Carmelo; Mangiola, Annunziato; De Bonis, Pasquale
Graphical abstract: Highlights: ENTs exploit safe recesses with less troubles to steer instruments in the nasal phase. Teamwork with ENTs allows a gradual learning curve with optimal clinical outcomes. Trainings mean more confidence with supra-/parasellar lesions less blood transfusions. Abstract: For neurosurgeons, who are accustomed to the binocular microscope, there is a new learning curve that must be overcome for monocular endoscopic pituitary surgery. Different studies describe a learning curve between 15 and 200 procedures, after which both operative time and complications stabilize. In this retrospective study, we evaluate the endoscopic learning curve of our group, already trained in microsurgical transsphenoidal surgery, with the assistance of ear, nose, and throat (ENT) surgeons. From 2010 to 2015, a total of 95 patients with pituitary adenomas were treated with a purely endoscopic approach. The latest 48 patients treated with the endoscope (L group) were compared with the 47 initial patients treated with the endoscope (E group) and with 43 patients treated with the microscope (M group), in terms of surgical time, complications, and tumor removal rate. The complication rate was similar in all the groups, as was the rate of total adenoma resection. Mean surgical time was shorter in the L group than in the E group (115 ± 36 min vs. 157 ± 46 min, p   <  0.001); the average operative time was also shorter in the L group than in the M group (135 ± 43 min). The estimated reduction in duration of surgery per 10 patients was 9 min ( p  < 0.001). Over time, blood transfusions discrepantly increased from the E group to the L group (11% vs. 31%). Because of the pivotal role of ENT in the transnasal stage of 50 endoscopic procedures, we obtained an operative time comparable to that of microscopic procedures, with similar complication rate and gross total resections. Neurosurgical-ENT combined follow-up proved to be a fundamental protection from late complications.